Use of recombinant proteins for the diagnosis and prevention of Mycoplasma bovis: a systematic review - Gomes, Camila Pachêco; da Silva, Lucas Santana Coelho; Santos Júnior, Manoel Neres; Barbosa, Maysa Santos; Neves, Wanderson Souza; Ribeiro, Viviane Gomes; Bastos, Bruno Lopes; Marques, Lucas Miranda (Frontiers in Veterinary Science, 2024)
IntroductionMycoplasma bovis is a highly contagious pathogen that causes various diseases in herd animals, negatively impacting reproduction, production, and milk yield. Effective diagnostic methods and vaccine development are critical for controlling M. bovis outbreaks. This systematic review aimed to evaluate diagnostic alternatives and vaccine compounds based on recombinant proteins.MethodsFollowing the PRISMA protocol, a systematic search was conducted in the SciELO, PubMed, and CAPES Periodicals Portal databases. Inclusion criteria included studies published between 2008 and 2023 that involved (1) the use of recombinant proteins for M. bovis identification or vaccine production, (2) biological samples, (3) availability in the selected databases, (4) in vitro or in vivo experimental designs, and (5) English-language publications.ResultsTen of the initial 53 studies screened met the inclusion criteria. Of these, four studies focused on diagnostic approaches and six on vaccine development. Diagnostic studies predominantly used an indirect enzyme-linked immunosorbent assay (ELISA) with recombinant proteins, achieving over 90% sensitivity and specificity in detecting M. bovis infections. In contrast, the development of recombinant vaccines has shown limited success, with challenges in identifying effective adjuvants and optimizing conditions for protective immunity.DiscussionWhile recombinant protein-based diagnostics have proven effective, developing a successful vaccine against M. bovis remains elusive. Further research is necessary to refine vaccine formulations, including selecting suitable adjuvants and challenge models to enhance protective efficacy against M. bovis infections.